1999
DOI: 10.1002/(sici)1097-0231(19990530)13:10<865::aid-rcm570>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The application of fast gradient capillary liquid chromatography/mass spectrometry to the analysis of pharmaceuticals in biofluids

Abstract: Fast gradient capillary high performance liquid chromatography (HPLC) coupled to a mass spectrometer has been successfully used for the analysis of pharmaceutical compounds from biological matrices, in the femtogram on column range. In the work reported in this paper, the use of capillary HPLC, on the 180-micron internal diameter scale, has shown a 30-fold improvement in detection limits when compared to conventional 2-mm scale chromatography. The use of fast gradient elution resulted in a generic methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…After the LC/MS/MS method has been optimized in terms of the composition of the LC mobile phase, mass spectrometric parameters and chromatographic peak efficiency, there is normally little that the bioanalyst can do to further improve the sensitivity. One area that is now attracting closer attention for this purpose is the use of capillary LC columns for bioanalytical LC/MS/MS methods Zell et al, 1997;Abian et al, 1999;Plumb et al, 1999;Fraser et al, 1999;Zhou et al, 2000). For an electrospray mass spectrometer, which tends to behave as if it were a concentration-sensitive detector (Abian et al, 1999), a 100-fold increase in the analyte peak concentration in the detector can theoretically be achieved by simply reducing the diameter of the LC column from 2 mm, which is currently in common use, to a capillary column dimension of 0.2 mm.…”
Section: Capillary Lcmentioning
confidence: 99%
“…After the LC/MS/MS method has been optimized in terms of the composition of the LC mobile phase, mass spectrometric parameters and chromatographic peak efficiency, there is normally little that the bioanalyst can do to further improve the sensitivity. One area that is now attracting closer attention for this purpose is the use of capillary LC columns for bioanalytical LC/MS/MS methods Zell et al, 1997;Abian et al, 1999;Plumb et al, 1999;Fraser et al, 1999;Zhou et al, 2000). For an electrospray mass spectrometer, which tends to behave as if it were a concentration-sensitive detector (Abian et al, 1999), a 100-fold increase in the analyte peak concentration in the detector can theoretically be achieved by simply reducing the diameter of the LC column from 2 mm, which is currently in common use, to a capillary column dimension of 0.2 mm.…”
Section: Capillary Lcmentioning
confidence: 99%
“…Although in a previous paper8 we described the limitations of the standard mass spectrometer source for capillary HPLC and how this problem was overcome, the new Sciex source required no such adaptation and could be used unmodified. The auxiliary gas was not required and the nebuliser gas pressure was reduced when compared to that used for standard HPLC flow rates.…”
Section: Resultsmentioning
confidence: 99%
“…The explosion of interest in capillary LC (cLC) and nano-LC the field of proteomic sciences provided the impetus for many instrument companies to develop dedicated microscale LC systems. Adapted with permission from [39,40] © John Wiley and Sons (1999).…”
Section: Early Applications Of Capillary Lcmentioning
confidence: 99%
“…These improvements in assay sensitivity overshadowed, and negated, the benefits that could be achieved by cLC, especially in development drug metabolism and PK (DMPK), as there was little or no sample volume issue. Also, the lack of a commercial integrated cLC-MS solution resulted in most improvements being 'home grown' (Figure 1) [39] and thus not easily implemented in a regulated environment. Nevertheless, Fraser et al showed in 1999 the benefits of cLC connected to an 'in-house' electrospray source previously described by Plumb and Dear for the quantification of a candidate pharmaceutical in rodents following serial tail bleeding ( Figure 2) [40].…”
mentioning
confidence: 99%